Maternal cardiac function in women at high risk for pre‐eclampsia treated with 150 mg aspirin or placebo: an observational study. (25th March 2020) - Ling, HZ; Jara, PG; Bisquera, A; Poon, LC; Nicolaides, KH; Kametas, NA
Abstract : Objective: To compare maternal haemodynamics in women at low and high risk for preterm pre‐eclampsia (PE), and between those at high risk who are randomised to aspirin or placebo. Design: Prospective, longitudinal observational study. Setting: Maternity units in six UK hospitals. Population: Women participating in the Aspirin for Prevention of Preterm Pre‐eclampsia (ASPRE) trial. The population comprised three groups of women: low risk for preterm PE ( n = 1362), high risk for preterm PE treated with aspirin ( n = 208) and high risk for preterm PE on placebo ( n = 220). Methods: Women had four visits during pregnancy: 11–14, 19–24, 30–34, and 35–37 weeks' gestation. Blood pressure was measured with a device validated for pregnancy, and PE and maternal haemodynamics were assessed with a bioreactance monitor at each visit. A multilevel linear mixed‐effects analysis was performed to examine longitudinal changes of maternal haemodynamic variables, controlling for demographic characteristics, past medical history and medication use. Main outcome measures: Longitudinal changes of cardiac output (CO), mean arterial pressure (MAP), and peripheral vascular resistance (PVR). Results: The low‐risk group demonstrated the expected changes with an increase in CO and reduction in MAP and PVR, with a quadratic change across gestation. In contrast, the high‐risk groups had a declining CO, and higher MAP and PVR during pregnancy. The administration of aspirin did not appear to affect maternal haemodynamics. Conclusions: Women screened as high risk for preterm PE have a pathological cardiac adaptation to pregnancy and the prophylactic use of aspirin (150 mg oral daily from the first trimester) in this group may not alter this haemodynamic profile. Tweetable abstract: In women at high risk of pre‐eclampsia, prophylactic use of aspirin may not alter the impaired maternal cardiac adaptation. Tweetable abstract: In women at high risk of pre‐eclampsia, prophylactic use of aspirin may not alter the impaired maternal cardiac adaptation.